2022
DOI: 10.1155/2022/1967675
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of rpoB, katG, and inhA Gene Polymorphisms Associated with Multidrug-Resistant Mycobacterium tuberculosis Complex Isolates among Ethiopian TB Patients: A Systematic Review

Abstract: Tuberculosis (TB) is one of the top 10 causes of mortality and the first killer among infectious diseases of poverty (IDoPs) worldwide. It disproportionately affects on-third of the world’s low-income countries including Ethiopia. One of the factors driving the TB epidemic is the global rise of MDR/XDR-TB and their low detection affect the global TB control progress. Recently, the resistance-associated genetic mutations in MTBC known to confer drug resistance have been detected by rapid molecular diagnostic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The present study reported 4 cases of multidrug resistance, of which the majority (14%) of mutations were observed at the S315T codon of the katG gene, followed by mutations at the H526D (9.1%) and H516D (6, 1%) of the rpoB and C15T genes (4.5%) of the inhA gene. Several previous research works have reported similar cases of multidrug resistance associated with mutations [14,[32][33][34].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The present study reported 4 cases of multidrug resistance, of which the majority (14%) of mutations were observed at the S315T codon of the katG gene, followed by mutations at the H526D (9.1%) and H516D (6, 1%) of the rpoB and C15T genes (4.5%) of the inhA gene. Several previous research works have reported similar cases of multidrug resistance associated with mutations [14,[32][33][34].…”
Section: Discussionmentioning
confidence: 57%
“…Extracted DNA was stored at -20°C until processing. [14][15][16][17][18] Detection of Tuberculosis by the TB-LAMP Automaton TB-LAMP is a molecular diagnostic technique that has enabled sensitive and accurate detection of tuberculosis. It is easy to use and gives reliable results within an hour.…”
Section: Framework Of the Study And Conduct Of The Research Workmentioning
confidence: 99%
“…The origin of development of drug-resistant tuberculosis (DR-TB) and the transmission, whether direct or by other means, especially in developing countries, are triggered by factors such as immune-compromised HIV individuals, poor living conditions, poor sanitation and acceptable hygiene, poor healthcare administration (diagnostic tools and delaying drug susceptibility testing (DST) practices), inadequate administration of anti-TB therapy regimens and patient compliance, high prevalence of diabetes mellitus, alcoholism, and smoking [ 23 , 24 , 25 ]. Seid et al [ 26 ] reported that the choice of GenoType MTBDRplus, MTBDRsl LPAs, and WGS as diagnostic techniques have proven to be efficient in the detection of specific genes that are responsible for triggering mutation by anti-TB drug resistance by reducing the timeframe in a matter of hours, instead of weeks or months as is traditionally known across the globe. The prevalence of anti-TB drug resistance among all diagnosed TB patients was 3637 (7%), while the prevalence of any RIF and INH resistance was 3460 (7%) and 2995 (6%), respectively [ Table 1 ] in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In RIF-resistant M. tb strains, the most common mutations were found in the following order: rpoB S450L probe (355 cases), Ile 491 Phe (35), and L430P (34 cases), with the remaining probes reporting single cases each. In a review by Seid et al [ 26 ], it was reported that most of the mutations were found in codons 531 (34.01%), 526 (9.3%), and 516 (2.33%) in the RIF resistance-determining region (RRDR) of the rpoB gene, and those related to RIF-resistance were in codon 531, followed by 526, mutations. These findings were not far from the findings of this study as the codon’s points were not far apart.…”
Section: Discussionmentioning
confidence: 99%
“… 16 To the best of our knowledge, identifying the drug resistance and conferring mutations with fitness cost in M. tuberculosis is helpful in controlling the spread of DR-TB. Limited studies have taken into account that the prevalence of genetic variants likely varies by setting as defined somewhere 20 ; however, the association of HIV co-infection with the fitness cost of genetic variants is unknown. 21 The aim of the study was to assess the association between the drug resistance-conferring genetic mutations with fitness cost and TB/HIV co-infection as well as to determine the performance characteristics of a diagnostic MTBDRplus v2.0 test.…”
Section: Introductionmentioning
confidence: 99%